Performance evaluation of looped tube thermoacoustic power generator using cyclic analysis - Gaikwad, Mahesh K.; Shinde, Savita U.; Naidu, Mithul J.; Jadhav, Tushar A.; Kumar, Rakesh; Salunkhe, Sachin; Cep, Robert; Abouel Nasr, Emad (Frontiers in Mechanical Engineering, 2024)
This paper focuses on the numerical and experimental investigation of the small-scale power generator. The travelling wave thermoacoustic power generator is numerically analyzed and experimentally tested. The cyclic analysis is used to carry out numerical analysis of the power generator. The system is operated on atmospheric pressure, which allows the manufacturing of an acoustic feedback loop using PVC piping. The acoustic power generated inside the generator is harnessed by the low-cost linear alternator, i.e. loudspeaker. The effect of regenerator wire mesh on performance of the power generator is numerically analyzed and validated experimentally. The numerical analysis identifies the temperature variation, pressure fluctuation, volume flow rate inside the system, and acoustic power distribution. The maximum electric power experimentally generated by the small-scale power generator is around 45 W with overall efficiency 8.30%. The alternator generates the maximum electric power at the optimum location, i.e. 2.30 m away from the engine core.